Role of Muslim Women in Countering Terrorism and Violent Extremism - Sabreen; Niazi (مجلة العلوم الإسلامية والدينية, 2022)
Acts of terrorism and violent extremism have become rampant in the recent past not only in Pakistan but worldwide. Efforts are on the way to counter terrorism and violent extremism. Mostly such efforts focus on the role of men while neglecting the role of half of the population i.e. the women. Women are influential in families, the workplace, institutions and communities so their role is very important. Acts of terrorism and violent extremism cannot be countered only by law enforcement agencies but by building social capacity to make such acts and actors unacceptable in society. In Pakistan’s context, Muslim women can play a very important role in achieving this purpose. Research has shown that women are the first respondents to extremist behaviour. They can play a very effective role in the prevention of the radicalization of young minds. While designing antiterrorism and antiviolence policies gender perspectives should be brought into consideration. Women empowerment can play a key role in identifying extremist behaviour and in the prevention of radicalization of young individuals. This research paper will analyze the role of women in countering terrorism and violent extremism and will propose a course for the future.